One step up and two steps back? The Italian debate on secularization, heteronormativity and LGBTQ citizenship - Bellè, Elisa; Peroni, Caterina; Rapetti, Elisa (2018)
The aim of this article is to furnish insights of the Italian public debate on the recognition of LGBTQ rights, which can be understood as an interesting case study of the complex relationship between (multi)secularisation processes and re/definition of citizenship models. More specifically, the article analyses two political events related to this debate that took place in Rome in June 2015. The first is the Family Day demonstration, promoted by conservative Catholic groups; the second is the LGBTQ Pride parade, promoted by various gay, lesbian and transsexual/gender associations. We analyse the official statements issued by the two organising committees of the demonstrations, adopting the framework and methods of the Critical Discourse Analysis. Above and beyond an evident political conflict between the two discourses, we try to shed light on their mutual construction on the basis of what we call naturalization' and universalization' processes.
Keywords: LGBTQ movements; analyse critique du discours; citoyenneté sexuelle et intime; Critical Discourse Analysis; Gender Equality; Laïcité; mouvement LGBTQ; mouvement catholique néo-fondamentaliste; neo-conservative Catholic movements; Secularisation; sexual and intimate citizenship; égalité de genre